2019
DOI: 10.2147/dmso.s214787
|View full text |Cite
|
Sign up to set email alerts
|

<p>Anthropometric variables as cardiovascular risk predictors in a cohort of adult subjects with Turner syndrome</p>

Abstract: Background and purposeExcessive adiposity is associated with cardiometabolic complications in Turner syndrome (TS) subjects. Reference data for predictive anthropometric indices of overweight/obesity and metabolic syndrome (MetS) are lacking for subjects with TS. The purpose of this study was to identify the best anthropometric predictor of cardiometabolic risk in a Latin-American cohort of TS subjects.Patients and methodsThis was a cross-sectional correlational study conducted in adult TS subjects (n=88) over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
1
14
0
2
Order By: Relevance
“…Body fat assessment by bioelectrical impedance analysis was estimated using a segmental two-frequency bioimpedance analyzer (Inbody 120; Biospace Industry, Seoul, South Korea) by a trained investigator (F.A.N.) according to a standard protocol described elsewhere (10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Body fat assessment by bioelectrical impedance analysis was estimated using a segmental two-frequency bioimpedance analyzer (Inbody 120; Biospace Industry, Seoul, South Korea) by a trained investigator (F.A.N.) according to a standard protocol described elsewhere (10).…”
Section: Methodsmentioning
confidence: 99%
“…An appointment was given for each subject during which clinical evaluation and anthropometric measurements were performed and recorded by a single experienced physician (F. A.-N.) according to a standard protocol described elsewhere (10). Each participant was tested individually.…”
Section: Design Study and Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 In POI, this relationship is more convoluted, as there are other discernible factors impacting metabolism in addition to estrogen. Limited studies examining body composition in POI have revealed conflicting data with some showing increasing adiposity, 40,41 while others did not. 42,43 Albeit, the common observation is that women who have early or premature menopause are at risk of losing bone and muscle mass culminating in increased fracture risk.…”
Section: Estrogen Action On Body Compositionmentioning
confidence: 99%
“…Los avances que se han realizado en materia de antropometría han permitido plantear nuevas fórmulas que permitan generar patrones de distribución de la grasa corporal como comportamental que ayuden a identificar con precisión dicha problemática (Álvarez-Nava et al, 2019), (Qing, Wei, Chan, Xiaoya, & Xin, 2017). Dichas fórmulas se relacionan con los índices de adiposidad corporal, índices de conicidad, índice de volumen abdominal y el índice CUN-BAE.…”
Section: Introductionunclassified